Syphilitic Popliteal Pseudoaneurysm Complicated by Acute Lower-Limb Ischemia. (January 2022) - Arasu, Rohan; Baimatova, Irina; Cohen, Toby
Case presentation: We present a case of a patient with a syphilitic popliteal pseudoaneurysm who developed acute lower-limb ischemia secondary to thromboembolism related to the pseudoaneurysm. The diagnosis of a syphilitic popliteal aneurysm was made due to positive syphilitic serological testing and with exclusion of all other potential causes. The pseudoaneurysm was surgically repaired using a great saphenous vein patch angioplasty, which was done without delay to prevent further thromboembolic complications. This was then followed by a course of intravenous benzyl penicillin.Discussion: Peripheral arterial involvement of tertiary syphilis remains exceedingly rare, with the vast majority of reported cases of vascular syphilis relating to aortic involvement. Given the paucity of literature on this condition, there is no good evidence to guide current management.Conclusion: With the globally increasing rates of syphilis, more cases of peripheral arterial involvement may become apparent, as was the case in the early 20th century.